The job market for transsexuals and Transvestites: a scope review protocol (Research, Society and Development, 2022)
Objective: Present the scope review protocol that aims to investigate how transsexuals and transvestites are inserted in the job market. Method: It is a scope review protocol, will be carried out following the recommendations of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic reviews and Meta – Analyses Extension for Scoping Reviews (PRISMA-ScR). Through the PCC strategy, the research question was elaborated for the subsequent review, with the population composed of transvestites and transsexuals; the Concept: working conditions, the labor market and labor relations; and the Context: the labor market, from the perspective of formal and informal relationships. Therefore, the guiding question of this review is: “How are transsexuals and transvestites inserted in the job market?”. The chosen databases were: Pubmed, Scielo, Scopus, Web of Science and Grey Literature Database. The search strategy - including all the descriptors contained in DECS and MESH - was adapted for each database and information source also included. Articles from periodicals and documents from the last ten years (2012-2021) will be included, in any language, that have transsexuals and transvestites as their study population, and that address the market, relationships and working conditions in their scope. and how this population is inserted. All the steps and data collected will be organized using tables, charts and flowcharts. This study will be carried out between April and July 2022.